The role of foreign direct investment, financial development, democracy and political (in)stability on economic growth in West Africa - Hammed Agboola Yusuf; Waliu Olawale Shittu; Saad Babatunde Akanbi; Habiba MohammedBello Umar; Idris Abdulganiyu Abdulrahman (International Trade, Politics and Development (ITPD), 2020)
Purpose - In this research, we examine the role of financial development, FDI, democracy and political instability on economic growth in West Africa. Design/methodology/approach - The study uses the dynamic fixed effects technique on the secondary data obtained from 1996 to 2016. Findings - Our empirical findings suggest that even though no significant relationship is established in the short run, the long-run coefficient of FDI is found to be significant and positive; a 1% increase in FDI inflow into the West African sub-region results in a 0.26% increase in economic growth. The coefficient of democracy is significant neither in the short run nor in the long run, but political instability is found to significantly and negatively impact the growth of the countries. Finally, the estimate of financial development-growth nexus follows the supply-leading hypothesis. Research limitations/implications - This research affirms the proposition that FDI is a relevant means of technology and knowledge transfers, thus resulting in increasing returns to production as a result of productive spillovers, which drives the growth of the economy. Consequently, an efficient institution - where the rule of law, political stability and economic freedom are top priorities - is a key to accelerate the growth of the West African economy. Similarly, we confirm the validity of the supply-leading hypothesis in West Africa. As such, by deepening the financial system, the growth of the subregion is propelled because an efficient financial system is a basis for sustainable development. Practical implication - The applicable policies are those that promote growth through FDI, financial development, democracy and political instability. The governments of West African countries are enjoined to promote policies that attract FDI into the subregion and promote financial sector credits so that economic performances may be enhanced. In addition, the governments of West African subregion should fully entrench democratic practices and enhance a stable and sustainable political environment. This will not only restore investor confidence but will also facilitate the inflow of FDI into the West African economy. Originality/value - Our study is the first to jointly examine these important growth determinants, especially in the context of West Africa. This becomes necessary in order to open the eyes of policy makers to the need for entrenched full democracy and to proffer sustainable cures to the frequent unrests in the subregion. The use of Pesaran (2007) technique of unit root is also a deviation from several existing studies. One advantage of this technique over others is that being a second-generation test, it tests variable unit root in the presence of crosssectional dependence.
Keywords: F2; G2; 330; Foreign direct investment; Financial development; West Africa; Economic growth; Institutions